Reconstructing Herbart's Teaching Method Based on Islamic Values: A Case Study at Darussalam Gontor Modern Islamic Boarding School. - Yusron, Moh Alwi; Anwar, Saiful; Wardhani, Ayu Era (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
This study examines the integration of Johann Friedrich Herbart's educational methods with Islamic values at Pondok Modern Darussalam Gontor, a prominent Islamic boarding school in Indonesia. Herbart's pedagogical framework, emphasizing structured teaching through five stages. preparation, presentation, association, generalization, and application. aligns with Islamic educational principles that focus on character development and comprehensive personal growth. Research Methods: The research employs a qualitative approach, utilizing literature review and case study methods. Data were collected through document analysis of Gontor's educational materials, observations of teaching practices, and interviews with educators and students to understand the implementation of Herbartian methods within an Islamic educational context. Findings: 1) Integration of Teaching Methods. 2) Balanced Curriculum. 3) Foreign Language Proficiency. 4) Comprehensive Evaluation. 5) Holistic Approach. This study highlights the successful integration of Western educational methods with Islamic values, offering a model for other educational institutions aiming to develop holistic and integrative learning systems. However, the research is limited to a single case study at Gontor; further studies could explore similar integrations in different educational settings to validate and expand upon these findings. The research provides a novel insight into how Herbart's educational concepts can be harmonized with Islamic principles, resulting in a comprehensive and effective educational system. This integration equips students with knowledge, skills, and character aligned with religious guidance and the demands of modern society.